Robust Algorithms for Formation Flying Reconfiguration (Global Journals of Research in Engineering, 2012)
Over the last 20 years spacecraft formation flying has been the subject of numerous research activities due to the advantages offered when compared with large, complex, single purpose satellites. With the obvious advantages of increased functionality and enhanced reliability, come however, also substantial challenges in the maintenance and reconfiguration of the spacecraft formation. The present paper addresses these problems by proposing two approaches that can be mathematically validated thus making it attractive for safety critical applications such as proximity operations. The first approach hinges on the implementation of pursuit algorithms first studied by French scientist Pierre Bouguer in the 18th century. The proposed approach separates the control law into two distinct stages: planar movement control and orthogonal displacement suppression. The second approach relies on the use of motion camouflage which is a hunting technique widely used in the natural world that allows a predator to approach a prey while appearing to remain stationary. A number of different scenarios are presented and the two approaches implemented within them. Numerical results shows that both methods are robust to dynamical uncertainties and do ensure the correct reconfiguration manoeuvres.
Keywords: spacecraft; complex; reconfiguration; substantial; orthogonal